198 - INTEGRATING THE EPIDEMIC SURVEILLANCE INTO THE ADVISORY COMMISSIONS IN A PEDIATRIC ACADEMICAL HOSPITAL (Fiep Bulletin - online, 2011)
The Surveillance Epidemic search to know, to detect or to prevent offences to the health individual or collective tends as purpose to recommend and to adopt the prevention measures and control. Those actions in the hospital atmosphere become fundamental tools for the continuous evaluation of the attendance to the health. This study tells the implantation experience of the Nucleus of Surveillance to the Health (NUVISA) in a Pediatric Academicals Hospital of the State of North Big Rio. The objective is to describe the process of operation of an unit organize that integrates and it articulates the actions of the Services of Epidemic Surveillance and Advisory Commissions of an Hospital Institution. It is a descriptive study of analysis. The implantation of NUVISA involved the united planning of actions and goals for the Services of Epidemic Surveillance and Advisory Commissions, the accompaniment and evaluation of the quality of the attendance rendered the child and the adolescent, through the definition of indicators, made a pact in meeting, to be used by each commission and service and the production and popularization of epidemic bulletins that integrate the information and indicators. As result, an epidemic profile of the hospital was defined, I diagnose it of the quality of the attendance to the health rendered the child and the adolescent, creating opportunities for the adoption of interventions with view to improve the indicators, to allocate resources in priority areas and to assist the real needs of the population.
Keywords: Surveillance to the health; quality of the attendance; pediatrics